Cell-based meat: The molecular aspect - Azhar, Asim; Zeyaullah, Md.; Bhunia, Shushruta; Kacham, Santhosh; Patil, Girish; Muzammil, Khursheed; Khan, Mohammad Suhail; Sharma, Sandeep (Frontiers in Food Science and Technology, 2023)
Cellular agriculture is one of the evolving fields of translational biotechnology. This emerging science aims to solve the issues related to sustainable food products and food security, lessen greenhouse gas emissions and improve animal well-being by circumventing livestock farming through cell-based meat (CBM) production. CBM can be manufactured utilizing cell culture techniques and biomanufacturing methods by exploiting mammalian cell lines. The cell-based products can also meet the demand for nutritional protein products for human consumption and pet animals. However, substantial advancement and modification are required for manufacturing CBM and related products in terms of cost, palatability, consumer acceptance, and safety. The current review discusses various aspects of molecular biology involved in establishing cell lines, myogenesis, regulation, scaffold, and bioreactor other associated approaches.